Linking Hospital and Tax data to support research on the economic impacts of hospitalization. (2017) - Sanmartin, Claudia; Reicker, Alexander; Garland, Allan; Iwashyna, Theodore; Fransoo, Randy; Scales, Damon; Wunsch, Hannah; Forget, Evelyn; Qiu, Hanqing
No abstract available